HARASPACE’S ACCOUNTING SYSTEM USING MICROSOFT ACCESS - Supriyanto Supriyanto; Kennily Kho (ConCEPt - Conference on Community Engagement Project, 2022)
Haraspace is a company that specializes in branding consulting with a concentration on food photography and videography. Haraspace has been running since 2019 and is located in Ruko Royal Sincom Blok A No. 03, Tlk. Tering, Batam Kota. Haraspace has decided to participate in community service initiatives as a partner (PkM). Haraspace had issues recording its company's accounting in its operational operations, which led in erroneous financial information and hampered the efficacy of its operational activities. Based on these issues, Haraspace's Microsoft Access-based accounting system was created to meet their demands. The system can generate profit or loss statement, statement of financial position, cash flow statement, trial balance, revenue report, purchase reports, debtors account, and creditors account, among other reports that explain the company's financial status. This accounting system may also generate relevant and reliable accounting data to help business owners make better business decisions. Future researchers can continue their work by migrating to a web-based system, which will simplify accounting records and allow users to access the system from any location at any time.